Singularities of digital flexor tendons in the Catalan Pyrenean Horse - Parés-Casanova, Pere M.; Bermúdez, Enara (Revista de Ciências Agroveterinárias, 2020)
The gross anatomy of the digital flexors tendons and the distal accessory ligament of the Catalan Pyrenean Horse, an equine trait breed from Catalonia (NE Spain), is presented here. Research has been based on the dissection of isolated 10 right forelimbs, 10 left forelimbs, six right hindlimbs and five left hindlimbs (total 31 distal limbs) from clinically normal yearlings, about 12 months of age. Tendons dimensions tended to be bigger than those reported in the literature, probably due to breed, age, bodyweight, withers height and exercise programme. Distal accessory ligament was sometimes absent. Data intend to serve as standard manual data for this breed but also for other trait breeds, being the present study the first one on the subject.